All solid state battery
A low-melting positive electrode current collector in all-solid-state batteries addresses the heat generation issue during internal short circuits by actively fusing to block electron flow, improving safety.
Patent Information
- Application Number
- JP2020200375
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-02
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-12-02
AI Technical Summary
All-solid-state batteries generate excessive heat during internal short circuits due to current flow, posing safety risks.
Employ a low-melting positive electrode current collector with a melting point between 170°C and 420°C, which actively fuses to interrupt electron conduction paths during a short circuit, reducing heat generation.
The use of a low-melting positive electrode current collector effectively minimizes heat generation during internal short circuits, enhancing safety by cutting off electron conduction.
Smart Images

Figure 0007615641000002 
Figure 0007615641000003 
Figure 0007615641000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to all-solid-state batteries. [Background technology]
[0002] An all-solid-state battery is a battery that has a solid electrolyte layer between a positive electrode active material layer and a negative electrode active material layer, and has the advantage that it is easier to simplify safety devices compared to liquid batteries that have an electrolyte solution containing a flammable organic solvent.
[0003] It is known that metals are used as a positive electrode current collector that collects current from a positive electrode active material layer and as a negative electrode current collector that collects current from a negative electrode active material layer. For example, Patent Document 1 discloses an electrode for an all-solid-state lithium battery that includes a metal layer, a conductive resin layer provided on the metal layer, and an active material layer provided on the conductive resin layer, and discloses that aluminum foil is used as the positive electrode metal layer and aluminum foil or tin foil is used as the negative electrode metal layer.
[0004] Patent Document 2 discloses a negative electrode in which at least the surface of the negative electrode current collector layer that is in contact with the negative electrode composite layer is made of a material containing an alloy of copper and a metal (e.g., zinc, beryllium, tin) that has a higher ionization tendency than copper. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2009-289534 A [Patent Document 2] JP 2019-175838 A Summary of the Invention [Problem to be solved by the invention]
[0006] For example, when an internal short circuit occurs in an all-solid-state battery, a current flows due to the internal short circuit, and the all-solid-state battery generates heat. It is preferable that the amount of heat generated is small. The present disclosure has been made in consideration of the above-mentioned circumstances, and has as its main object to provide an all-solid-state battery that generates a small amount of heat even when an internal short circuit occurs. [Means for solving the problem]
[0007] The present disclosure provides an all-solid-state battery having a positive electrode active material layer and a low melting positive electrode current collector, the low melting positive electrode current collector containing a metal element and having a melting point of 170°C or higher and 420°C or lower.
[0008] According to the present disclosure, by using a low melting positive electrode current collector having a predetermined melting point, it is possible to obtain an all-solid-state battery that generates little heat even when, for example, an internal short circuit occurs.
[0009] In the above disclosure, the low melting point positive electrode current collector may contain, as the metal element, a first metal element having a melting point of 170° C. or more and 420° C. or less in its simple form.
[0010] In the above disclosure, the low melting point positive electrode current collector may contain at least one of Zn, Sn, Bi, Pb, Tl, Cd and Li as the first metallic element.
[0011] In the above disclosure, the low melting point positive electrode current collector may contain Zn as the first metallic element.
[0012] In the above disclosure, the low melting point positive electrode current collector may contain Sn as the first metallic element.
[0013] In the above disclosure, the low melting point positive electrode current collector may be a simple metal containing the above metal element.
[0014] In the above disclosure, the low melting positive electrode current collector may be an alloy containing the above metal element.
[0015] In the above disclosure, the alloy may contain a first metal element having a melting point of 170°C or more and 420°C or less in the simple metal state, and a second metal element having a melting point of more than 420°C in the simple metal state.
[0016] In the above disclosure, the low melting point positive electrode current collector may have a coating layer containing a carbon material on the surface on the positive electrode active material layer side.
[0017] In the above disclosure, the coating layer may contain an inorganic filler.
[0018] In the above disclosure, the all-solid-state battery may have a unit cell, the unit cell having a negative electrode current collector, a first structure arranged on one surface of the negative electrode current collector, and a second structure arranged on the other surface of the negative electrode current collector, the first structure having, in order from the negative electrode current collector side along the thickness direction, a first negative electrode active material layer, a first solid electrolyte layer, a first positive electrode active material layer, and a first positive electrode current collector, the second structure having, in order from the negative electrode current collector side along the thickness direction, a second negative electrode active material layer, a second solid electrolyte layer, a second positive electrode active material layer, and a second positive electrode current collector, and at least one of the first positive electrode current collector and the second positive electrode current collector may be the low melting positive electrode current collector.
[0019] In the above disclosure, the all-solid-state battery may have a plurality of unit cells, and the plurality of unit cells may be stacked along a thickness direction. In the plurality of stacked unit cells, when a positive electrode current collector located on the outermost side is an outermost positive electrode current collector, only the outermost positive electrode current collector may be the low melting positive electrode current collector. Effect of the Invention
[0020] The all-solid-state battery according to the present disclosure has an advantage that the amount of heat generated is small even when an internal short circuit occurs, for example. [Brief description of the drawings]
[0021] [Figure 1]FIG. 1 is a schematic cross-sectional view illustrating an all-solid-state battery according to the present disclosure. [Diagram 2] FIG. 2 is a schematic cross-sectional view illustrating a positive electrode according to the present disclosure. [Diagram 3] FIG. 1 is a schematic cross-sectional view illustrating an all-solid-state battery according to the present disclosure. [Figure 4] FIG. 1 is a schematic cross-sectional view illustrating a unit cell in the present disclosure. [Diagram 5] FIG. 1 is a schematic cross-sectional view illustrating an all-solid-state battery according to the present disclosure. [Figure 6] FIG. 1 is a schematic cross-sectional view illustrating an all-solid-state battery according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The all-solid-state battery in the present disclosure will be described in detail below with reference to the drawings. Each of the drawings shown below is a schematic illustration, and the size and shape of each part are appropriately exaggerated to facilitate understanding. In addition, in each of the drawings, hatching showing the cross section of a member is appropriately omitted. In addition, in this specification, when expressing an aspect in which another member is arranged relative to a certain member, simply writing "above" or "below" includes both a case in which another member is arranged directly above or below a certain member so as to be in contact with the certain member, and a case in which another member is arranged above or below a certain member via another member.
[0023] Fig. 1 is a schematic cross-sectional view illustrating an example of an all-solid-state battery according to the present disclosure. The all-solid-state battery 10 shown in Fig. 1 has a positive electrode active material layer 1, a positive electrode current collector 2 that collects current from the positive electrode active material layer 1, a negative electrode active material layer 3, a negative electrode current collector 4 that collects current from the negative electrode active material layer 3, and a solid electrolyte layer 5 disposed between the positive electrode active material layer 1 and the negative electrode active material layer 3. The positive electrode current collector 2 is a low-melting positive electrode current collector 2x having a predetermined melting point.
[0024] According to the present disclosure, by using a low melting positive electrode current collector having a predetermined melting point, for example, even if an internal short circuit occurs, an all-solid-state battery with a small amount of heat generation can be obtained. As described above, when an internal short circuit occurs in an all-solid-state battery, heat is generated in the all-solid-state battery due to the flow of current associated with the internal short circuit. Examples of reasons for the occurrence of an internal short circuit include the inclusion of conductive foreign matter (e.g., metal pieces) during battery manufacturing and piercing of the all-solid-state battery by a conductive member (e.g., a metal member).
[0025] The present inventors focused on the melting point of the positive electrode collector in order to reduce the amount of heat generated. Specifically, they came up with the idea of using a positive electrode collector with a low melting point (low melting positive electrode collector) as the positive electrode collector, and actively melting the positive electrode collector when heat is generated in the all-solid-state battery. In fact, it was confirmed that by using a low melting positive electrode collector, the electron conduction path is cut off by melting (shutdown function is expressed), and the amount of heat generated can be reduced. Conventionally, Al foil is widely known as a positive electrode collector, but since the melting point of Al foil is as high as 660°C, melting does not usually occur even if heat is generated due to current of an internal short circuit. In contrast, in the present disclosure, by using a low melting positive electrode collector, melting can be actively caused to occur, and the amount of heat generated can be reduced.
[0026] The portion where the low melting positive electrode collector melts is not particularly limited, but for example, when a conductive member is pierced as in a needle puncture test described later, melting occurs first in the area where the conductive member and the low melting positive electrode collector are in contact. Also, when a conductive foreign object present inside the battery is in contact with the low melting positive electrode collector, melting occurs first at the contact portion. Also, the shutdown function may be expressed by melting the low melting positive electrode collector as a whole or melting the tab portion of the low melting positive electrode collector due to heat generation.
[0027] For example, the voltage of a lithium-ion battery is 3.0 to 4.2 V (vs Li / Li) during charging. +), so metals that ionize at potentials lower than the standard electrode potential of -0.045 to 1.155 V (vs SHE) may corrode (Li: -3.045 V vs SHE). For example, the standard electrode potentials of Zn and Sn are as follows: Zinc 2+ +2e - =Zn(-0.7626V) Sn 2+ +2e - =Sn(-0.1375V) In particular, in the case of lithium-ion batteries using an electrolyte, metal elution becomes significant, and therefore corrosion occurs when Zn or Sn is used as the positive electrode current collector. In contrast, in the case of all-solid-state lithium-ion batteries, a solid electrolyte with no fluidity is used, so metal elution is unlikely to occur, and Zn or Sn can be used as the positive electrode current collector. In addition, in the case of lithium-ion batteries using an electrolyte, when Al (-1.7V) is used as the positive electrode current collector, an AlF3 coating is formed by the fluorine-containing compound (e.g. LiPF6) contained in the electrolyte, so that it can be used as the positive electrode current collector.
[0028] In particular, in all-solid-state batteries using a sulfide solid electrolyte, it has been common to use Al foil as a positive electrode current collector. This is because Al foil is not easily sulfurized and does not pose any major problems in use. In the present disclosure, it was only by focusing on actively fusing the positive electrode current collector that it was possible to adopt a low melting positive electrode current collector with a melting point lower than that of Al foil (660°C). In addition, the negative electrode current collector may deteriorate due to volume change caused by Li alloying during charging and discharging, but the positive electrode current collector does not usually undergo Li alloying during charging, so even if a low melting positive electrode current collector is used, it will not deteriorate due to volume change caused by Li alloying.
[0029] 1. Positive electrode The positive electrode in the present disclosure has a positive electrode active material layer containing a positive electrode active material, and a positive electrode current collector that collects current from the positive electrode active material layer.
[0030] (1) Positive electrode current collector The all-solid-state battery according to the present disclosure has, as a positive electrode current collector, a low-melting positive electrode current collector that contains a metal element and has a melting point of 170° C. or higher and 420° C. or lower.
[0031] The metal element contained in the low melting positive electrode current collector is not particularly limited. The low melting positive electrode current collector may contain only one type of metal element, or may contain two or more types. The low melting positive electrode current collector preferably contains, as the metal element, a first metal element whose melting point in the simple metal form is 170°C or more and 420°C or less. The low melting positive electrode current collector may contain only one type of the first metal element, or may contain two or more types. Examples of the first metal element include Zn, Sn, Bi, Pb, Tl, Cd, and Li.
[0032] The low melting positive electrode current collector may or may not contain a second metal element having a melting point of 420°C or higher as a metal element. Examples of the second metal element include Sb, Cu, Ag, Ni, and Ge. The low melting positive electrode current collector may or may not contain a third metal element having a melting point of 170°C or lower as a metal element. Examples of the third metal element include Cs, In, and Ga.
[0033] The low melting positive electrode current collector may be a metal element or an alloy. In the latter case, the low melting positive electrode current collector preferably contains at least the first metal element, and preferably contains the first metal element as a main component. The main component refers to the metal element that has the largest weight ratio among all the metal elements contained in the alloy. In addition, the low melting positive electrode current collector preferably contains Zn as a metal element, and preferably contains Zn as a main component. In addition, the low melting positive electrode current collector preferably contains Sn as a metal element, and preferably contains Sn as a main component.
[0034] The melting point of the low melting positive electrode collector is usually 170°C or higher, may be 180°C or higher, or may be 200°C or higher. If the melting point of the low melting positive electrode collector is too low, the low melting positive electrode collector may melt during the production of the all-solid-state battery. On the other hand, the melting point of the low melting positive electrode collector is usually 420°C or lower, and may be 350°C or lower. If the melting point of the low melting positive electrode collector is too high, the effect of blocking the electron conduction path due to the melting of the low melting positive electrode collector may not be sufficiently obtained.
[0035] Here, the melting point of Zn alone is 420° C., the melting point of Sn alone is 232° C., the melting point of Bi alone is 271° C., the melting point of Pb alone is 328° C., the melting point of Tl alone is 304° C., the melting point of Cd alone is 321° C., and the melting point of Li alone is 180° C. The melting point of the Sn—Sb alloy depends on the composition, but is, for example, about 240° C.
[0036] The shape of the low melting positive electrode current collector may be, for example, a foil or a mesh. The thickness of the low melting positive electrode current collector is, for example, 0.1 μm or more, and may be 1 μm or more. If the low melting positive electrode current collector is too thin, the current collecting function may be reduced. On the other hand, the thickness of the low melting positive electrode current collector is, for example, 1 mm or less, and may be 100 μm or less. If the low melting positive electrode current collector is too thick, the volume energy density of the all-solid-state battery may be reduced.
[0037] 2, the low melting positive electrode current collector 2x may have a coating layer 6 containing a carbon material on the surface on the side of the positive electrode active material layer 1. By disposing the coating layer 6 between the low melting positive electrode current collector 2x and the positive electrode active material layer 1, the contact resistance between them can be reduced.
[0038] The coating layer is a layer containing at least a carbon material. Examples of the carbon material include carbon black such as furnace black, acetylene black, ketjen black, and thermal black, carbon fibers such as carbon nanotubes and carbon nanofibers, activated carbon, carbon, graphite, graphene, and fullerene. The shape of the carbon material may be, for example, particulate. The ratio of the carbon material contained in the coating layer is, for example, 5% by volume or more and 95% by volume or less.
[0039] The coating layer may further contain a resin. For example, by adding a large amount of resin, a coating layer having flexibility can be obtained. Due to the high flexibility, the contact area between the coating layer on the positive electrode current collector and the positive electrode active material layer can be increased by the restraining pressure applied to the battery, and the contact resistance can be reduced. In addition, by adding a large amount of resin, a coating layer having PTC characteristics can be obtained. Here, PTC means Positive Temperature Coefficient, and the PTC characteristic refers to a characteristic in which the resistance changes with a positive coefficient as the temperature increases. That is, the resin contained in the coating layer expands in volume as the temperature increases, and the resistance of the coating layer increases. As a result, for example, even if an internal short circuit occurs, the amount of heat generated can be reduced.
[0040] Examples of the resin include thermoplastic resins. Examples of the thermoplastic resin include polyvinylidene fluoride (PVDF), polypropylene, polyethylene, polyvinyl chloride, polystyrene, acrylonitrile butadiene styrene (ABS) resin, methacrylic resin, polyamide, polyester, polycarbonate, polyacetal, and the like. The melting point of the resin is, for example, 80°C or higher and 300°C or lower. The proportion of the resin contained in the coating layer is, for example, 5% by volume or higher, and may be 50% by volume or higher. On the other hand, the proportion of the resin contained in the coating layer is, for example, 95% by volume or lower.
[0041] The coating layer may or may not contain an inorganic filler. In the former case, a coating layer with high PTC properties is obtained, and in the latter case, a coating layer with high electronic conductivity is obtained. In an all-solid-state battery, a confining pressure is usually applied along the thickness direction, so that the resin contained in the coating layer may deform or flow under the influence of the confining pressure, and the PTC properties may not be fully exhibited. In contrast, by adding a hard inorganic filler to the coating layer, the PTC properties are fully exhibited even when the coating layer is affected by the confining pressure.
[0042] Examples of inorganic fillers include metal oxides and metal nitrides. Examples of metal oxides include alumina, zirconia, and silica, and examples of metal nitrides include silicon nitride. The average particle size (D 50 ) may be, for example, 50 nm or more and 5 μm or less, or 100 nm or more and 2 μm or less. The content of the inorganic filler in the coating layer is, for example, 5 vol. % or more and 90 vol. % or less.
[0043] The thickness of the coating layer is, for example, 1 μm or more and 20 μm or less, and may be 1 μm or more and 10 μm or less.
[0044] (2) Positive electrode active material layer The positive electrode active material layer contains at least a positive electrode active material, and may contain at least one of a solid electrolyte, a conductive material, and a binder, as necessary.
[0045] Examples of the positive electrode active material include oxide active materials. Examples of the oxide active material include LiCoO2, LiMnO2, LiNiO2, LiVO2, and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, etc., rock salt layered active materials, LiMn2O4, Li(Ni 0.5 Mn 1.5 )O4, Li4Ti5O 12and olivine type active materials such as LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, etc. As the positive electrode active material, sulfur (S) or lithium sulfide (Li2S) may be used.
[0046] In addition, a protective layer containing a Li-ion conductive oxide may be formed on the surface of the positive electrode active material. This is because it can suppress the reaction between the positive electrode active material and the solid electrolyte. An example of the Li-ion conductive oxide is LiNbO3. The thickness of the protective layer is, for example, 0.1 nm to 100 nm, and may be 1 nm to 20 nm.
[0047] The shape of the positive electrode active material may be, for example, particulate. 50 ) is, for example, 10 nm or more and 50 μm or less, and may be 100 nm or more and 20 μm or less. The proportion of the positive electrode active material in the positive electrode active material layer is, for example, 50 wt % or more, and may be 60 wt % or more and 99 wt % or less.
[0048] Examples of the solid electrolyte include inorganic solid electrolytes such as sulfide solid electrolytes and oxide solid electrolytes. The sulfide solid electrolyte preferably contains Li, A (A is at least one of P, Si, Ge, Al, and B), and S. The sulfide solid electrolyte preferably has an anion structure with an ortho composition (PS4 3- Structure: SiS4 4- Structure, GeS4 4- Structure: AlS3 3- Structure, BS3 3- It is preferable that the sulfide solid electrolyte has an anion structure having an ortho composition as a main component of the anion. The ratio of the anion structure having an ortho composition is, for example, 50 mol% or more, and may be 70 mol% or more, based on the total anion structures in the sulfide solid electrolyte. The sulfide solid electrolyte may also contain a lithium halide. Examples of the lithium halide include LiCl, LiBr, and LiI.
[0049] The solid electrolyte may be glass, crystallized glass (glass ceramics), or a crystalline material. The shape of the solid electrolyte may be, for example, particulate.
[0050] Examples of the conductive material include carbon materials such as acetylene black (AB), ketjen black (KB), carbon fiber, carbon nanotube (CNT), and carbon nanofiber (CNF). Examples of the binder include rubber-based binders such as butylene rubber (BR) and styrene butadiene rubber (SBR), and fluoride-based binders such as polyvinylidene fluoride (PVDF). The thickness of the positive electrode active material layer is, for example, 0.1 μm or more and 300 μm or less, and may be 0.1 μm or more and 100 μm or less.
[0051] 2.Negative electrode The negative electrode in the present disclosure has a negative electrode active material layer containing a negative electrode active material and a negative electrode current collector that collects current from the negative electrode active material layer. The negative electrode active material layer contains at least the negative electrode active material, and may contain at least one of a solid electrolyte, a conductive material, and a binder, as necessary.
[0052] Examples of the negative electrode active material include metal active materials, carbon active materials, and oxide active materials. Examples of the metal active material include simple metals and metal alloys. Examples of the metal elements contained in the metal active material include Si, Sn, Li, In, and Al. The metal alloy is preferably an alloy containing the above metal elements as a main component. The metal alloy may be a two-component alloy, or a multi-component alloy of three or more components. Examples of the carbon active material include mesocarbon microbeads (MCMB), highly oriented graphite (HOPG), hard carbon, and soft carbon. Examples of the oxide active material include Li4Ti5O 12 Lithium titanates such as those mentioned above are also included.
[0053] The solid electrolyte, conductive material, and binder used in the negative electrode active material layer are the same as those described in "1. Positive electrode" above, and therefore will not be described here. The thickness of the negative electrode active material layer is, for example, 0.1 μm to 300 μm, and may be 0.1 μm to 100 μm.
[0054] Examples of the metal elements contained in the negative electrode current collector include Cu, Fe, Ti, Ni, Zn, and Co. The negative electrode current collector may be a simple metal element or an alloy containing the metal element as a main component. Examples of the shape of the negative electrode current collector include a foil shape and a mesh shape. The thickness of the negative electrode current collector is, for example, 0.1 μm or more and 1 mm or less, and may be 1 μm or more and 100 μm or less.
[0055] 3.Solid electrolyte layer The solid electrolyte layer is a layer disposed between the positive electrode active material layer and the negative electrode active material layer. The solid electrolyte layer contains at least a solid electrolyte, and may further contain a binder as necessary. The solid electrolyte and binder used in the solid electrolyte layer are the same as those described in "1. Positive electrode" above, and therefore will not be described here.
[0056] The content of the solid electrolyte in the solid electrolyte layer is, for example, 10% by weight or more and 100% by weight or less, and may be 50% by weight or more and 100% by weight or less. The thickness of the solid electrolyte layer is, for example, 0.1 μm or more and 300 μm or less, and may be 0.1 μm or more and 100 μm or less.
[0057] 4.All-solid-state battery The all-solid-state battery in the present disclosure has a unit cell. The term "unit cell" refers to a unit constituting a battery element in an all-solid-state battery, and has a positive electrode current collector, a positive electrode active material layer, a solid electrolyte layer, a negative electrode active material layer, and a negative electrode current collector. The positive electrode current collector in one unit cell may be common to the positive electrode current collector or the negative electrode current collector in another unit cell. Similarly, the negative electrode current collector in one unit cell may be common to the negative electrode current collector or the positive electrode current collector in another unit cell.
[0058] The all-solid-state battery in the present disclosure may have only one unit cell, or may have two or more unit cells. In the latter case, the multiple unit cells are usually stacked along the thickness direction. The multiple unit cells may be connected in series or in parallel. For example, the all-solid-state battery 10 shown in FIG. 1 has only one unit cell having a positive electrode current collector 2, a positive electrode active material layer 1, a solid electrolyte layer 5, a negative electrode active material layer 3, and a negative electrode current collector 4. On the other hand, the all-solid-state battery 10 shown in FIG. 3 has unit cells U1 and U2, which are connected in series. The intermediate current collector 7 shown in FIG. 3 serves both as the negative electrode current collector in the unit cell U1 and the positive electrode current collector in the unit cell U2. The intermediate current collector 7 may be the low melting positive electrode current collector (low melting current collector) described above.
[0059] FIG. 4 is a schematic cross-sectional view illustrating a unit cell in the present disclosure. The unit cell U shown in FIG. 4 has a negative electrode current collector 4, a first structure A arranged on one surface s1 of the negative electrode current collector 4, and a second structure B arranged on the other surface s2 of the negative electrode current collector 4. The first structure A has a first negative electrode active material layer 3a, a first solid electrolyte layer 5a, a first positive electrode active material layer 1a, and a first positive electrode current collector 2a in this order along the thickness direction from the negative electrode current collector 4 side. On the other hand, the second structure B has a second negative electrode active material layer 3b, a second solid electrolyte layer 5b, a second positive electrode active material layer 1b, and a second positive electrode current collector 2b in this order along the thickness direction from the negative electrode current collector 4 side. At least one of the first positive electrode current collector 2a and the second positive electrode current collector 2b is preferably the low melting positive electrode current collector described above.
[0060] 4, the configuration of the other layers is symmetrical with respect to the negative electrode current collector 4, so that stress caused by the difference in elasticity between the positive electrode active material layer and the negative electrode active material layer is unlikely to occur, and as a result, breakage of the negative electrode current collector can be suppressed.
[0061] The all-solid-state battery of the present disclosure may have a plurality of unit cells U shown in FIG. 4. The all-solid-state battery 10 shown in FIG. 5 has a plurality of unit cells U shown in FIG. 4 (unit cells U1 to U3), and the plurality of unit cells U are connected in parallel. Specifically, all the positive electrode collectors 2a and positive electrode collectors 2b in the unit cells U1 to U3 are electrically connected, and all the negative electrode collectors 4 in the unit cells U1 to U3 are electrically connected, so that the unit cells U1 to U3 are connected in parallel. It is preferable that at least one of the positive electrode collectors 2a and positive electrode collectors 2b in the unit cells U1 to U3 is the low melting positive electrode collector described above. In FIG. 5, the opposing positive electrode collectors 2a and positive electrode collectors 2b (for example, the positive electrode collector 2b in the unit cell U1 and the positive electrode collector 2a in the unit cell U2) are different members, but they may be the same member (one positive electrode collector).
[0062] On the other hand, the all-solid-state battery 10 shown in FIG. 6 has a plurality of unit cells U shown in FIG. 4 (unit cells U1 to U3), an insulating member 20 is disposed between each of the unit cells U, and the plurality of unit cells U are connected in series. Specifically, in the unit cells U1 to U3, the positive electrode current collector 2a and the positive electrode current collector 2b are electrically connected to each other, and further, the negative electrode current collector 4 in the unit cell U1 is electrically connected to the positive electrode current collector 2a and the positive electrode current collector 2b in the unit cell U2, and the negative electrode current collector 4 in the unit cell U2 is electrically connected to the positive electrode current collector 2a and the positive electrode current collector 2b in the unit cell U3. At least one of the positive electrode current collectors 2a and the positive electrode current collectors 2b in the unit cells U1 to U3 is preferably the low melting positive electrode current collector described above.
[0063] In addition, in the stacked unit cells, the positive electrode current collector located on the outermost side is the outermost positive electrode current collector. For example, in FIG. 5 and FIG. 6, the positive electrode current collector 2a in the unit cell U1 and the positive electrode current collector 2b in the unit cell U3 correspond to the outermost positive electrode current collector. In the present disclosure, the outermost positive electrode current collector is preferably a low melting positive electrode current collector. For example, when a conductive member is stuck into the all-solid-state battery and short-circuits, the contact area between the conductive member and the outermost positive electrode current collector becomes large. The amount of heat generated can be further reduced by blocking the electronic conduction path at the contact portion by melting the outermost positive electrode current collector. In addition, as shown in FIG. 5 and FIG. 6, when outermost positive electrode current collectors are present at both ends, at least one of the outermost positive electrode current collectors is preferably a low melting positive electrode current collector, and both may be low melting positive electrode current collectors. In addition, in the present disclosure, only the outermost positive electrode current collector may be a low melting positive electrode current collector. In this case, all the positive electrode current collectors other than the outermost positive electrode current collector may be high melting positive electrode current collectors having a melting point of more than 420°C.
[0064] The all-solid-state battery of the present disclosure may have an exterior body that houses the positive electrode, the solid electrolyte layer, and the negative electrode. The exterior body may or may not have flexibility. An example of the former is an aluminum laminate film, and an example of the latter is a SUS case.
[0065] In addition, the all-solid-state battery of the present disclosure may be subjected to a confining pressure by a confining jig. The confining pressure is, for example, 0.1 MPa or more, may be 1 MPa or more, or may be 5 MPa or more. On the other hand, the confining pressure is, for example, 100 MPa or less, may be 50 MPa or less, or may be 20 MPa or less.
[0066] In addition, the type of the all-solid-state battery in the present disclosure is not particularly limited, but is typically an all-solid-state lithium-ion secondary battery. Furthermore, the use of the all-solid-state battery in the present disclosure includes, for example, a power source for vehicles such as hybrid automobiles, electric automobiles, gasoline automobiles, and diesel automobiles. In particular, it is preferable to use it as a driving power source for hybrid automobiles or electric automobiles. In addition, the all-solid-state battery in the present disclosure may be used as a power source for moving bodies other than vehicles (for example, railways, ships, and aircraft), and may be used as a power source for electrical products such as information processing devices.
[0067] The present disclosure is not limited to the above-described embodiments. The above-described embodiments are merely examples, and anything that has substantially the same configuration as the technical idea described in the claims of the present disclosure and exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES
[0068] [Example 1] (Preparation of negative electrode) Anode active material (Si particles, average particle size 2.5 μm), sulfide solid electrolyte (10LiI·15LiBr·75 (0.75Li2S·0.25P2S5), average particle size 0.5 μm), conductive material (VGCF-H), and binder (SBR) were weighed out so that the weight ratio of anode active material:sulfide solid electrolyte:conductive material:binder was 62.1:31.7:5.0:1.2, and mixed with a dispersion medium (diisobutyl ketone). The mixture was dispersed with an ultrasonic homogenizer (UH-50, manufactured by SMT Co., Ltd.) to obtain a slurry. The obtained slurry was applied to anode current collector (Ni foil, thickness 22 μm) by a blade coat method using an applicator, and dried at 100 °C for 30 minutes. After that, 1 cm 2 The negative electrode active material layer and the negative electrode current collector were obtained by punching out the negative electrode active material layer to a size of 50 μm.
[0069] (Preparation of positive electrode) Positive electrode active material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 The positive electrode active material (Zn foil, 50 μm thick) was applied to a positive electrode current collector (Zn foil, 50 μm thick) by a blade coating method using an applicator, and the slurry was dried at 100°C for 30 minutes. The slurry was then applied to a positive electrode current collector (Zn foil, 50 μm thick) by a blade coating method using an applicator, and the ... 2 A positive electrode having a positive electrode active material layer and a positive electrode current collector was obtained by punching out the positive electrode active material layer to a size of 80 μm. The thickness of the positive electrode active material layer was 80 μm.
[0070] (Preparation of solid electrolyte layer) A sulfide solid electrolyte (10LiI 15LiBr 75 (0.75Li2S 0.25P2S5), average particle size 2.0μm) and a binder (SBR) were weighed out so that the weight ratio of sulfide solid electrolyte:binder was 99.6:0.4, and mixed with a dispersion medium (diisobutyl ketone). The mixture was dispersed with an ultrasonic homogenizer (UH-50, manufactured by SMT Corporation) to obtain a slurry. The obtained slurry was applied to an Al foil (thickness 15μm) by a blade coating method using an applicator, and dried at 100℃ for 30 minutes. The mixture was then poured into a 1cm 2 A solid electrolyte layer was obtained by punching out the aluminum foil into a size of 20 μm. The thickness of the solid electrolyte layer was 20 μm.
[0071] (Production of all-solid-state batteries) The obtained solid electrolyte layer and the obtained positive electrode active material layer were placed opposite each other and pressed at a linear pressure of 1.6 t / cm by a roll press method, and then the Al foil was peeled off from the solid electrolyte layer. This resulted in the solid electrolyte layer being transferred onto the positive electrode active material layer. The solid electrolyte layer transferred onto the positive electrode active material layer was placed opposite the negative electrode active material layer and pressed at a linear pressure of 5.0 t / cm by a roll press method. Then, current collecting tabs were placed on the positive electrode current collector and the negative electrode current collector, respectively, and laminated and sealed to obtain an all-solid-state battery.
[0072] [Example 2] An all-solid-state battery was obtained in the same manner as in Example 1, except that Sn foil (thickness: 50 μm) was used as the positive electrode current collector.
[0073] [Comparative Example 1] An all-solid-state battery was obtained in the same manner as in Example 1, except that an Al foil (thickness: 50 μm) was used as the positive electrode current collector.
[0074] [evaluation] A needle puncture test was performed on the all-solid-state batteries obtained in Examples 1 and 2 and Comparative Example 1. Specifically, the all-solid-state battery was restrained at 5 MPa using a restraining plate having a hole for needle puncture. Then, while performing CC-CV charging at 4.35 V (upper current limit 20 A), the all-solid-state battery was punctured with a needle having a diameter of 1 mm and a tip angle of 20° at a speed of 0.1 mm / s and a depth of 0.4 mm. The heat generation amount (W) was calculated from the product of the voltage (V) and the inflow current (A). The results are shown in Table 1.
[0075] [Table 1]
[0076] As shown in Table 1, it was confirmed that Examples 1 and 2 generated less heat than Comparative Example 1. This is presumably because the melting points of the positive electrode collectors used in Examples 1 and 2 were lower than that of the positive electrode collector used in Comparative Example 1, and the electron conduction path at the contact point between the positive electrode collector and the needle was blocked by the melting of the positive electrode collector during an internal short circuit.
[0077] [Reference example] The influence of dissolution of the positive electrode current collector was examined in the all-solid-state batteries obtained in Examples 1 and 2 and Comparative Example 1. Specifically, trickle charging was performed on the all-solid-state batteries at 60°C for 2 weeks at 4.35 V. Before and after trickle charging, the current was 5.2 mA / cm 2 (equivalent to 2C) for 10 seconds, and the resistance was calculated. The resistance increase rate was 106% for Comparative Example 1 (Al), 108% for Example 1 (Zn), and 107% for Example 2 (Sn). Since the resistance increase rates were equivalent in Examples 1 and 2 and Comparative Example 1, it was suggested that the effect of corrosion is limited in all-solid-state batteries. [Explanation of symbols]
[0078] 1... Positive electrode active material layer 2... Positive electrode current collector 3...Negative electrode active material layer 4 … Negative electrode current collector 5…Solid electrolyte layer 6 … Coat layer 10 … All-solid-state battery
Claims
1. An all-solid-state lithium ion battery having a positive electrode active material layer and a low melting positive electrode current collector, The low melting positive electrode current collector contains a metal element and has a melting point of 170° C. or more and 420° C. or less, The low melting positive electrode current collector is a metal element containing Zn or Sn as the metal element, The low melting positive electrode current collector has a thickness of 50 μm or less and a foil shape, The positive electrode active material layer contains a carbon material as a conductive material, an all-solid-state lithium-ion battery comprising, in order along a thickness direction, the low melting positive electrode current collector that collects current from the positive electrode active material layer, the positive electrode active material layer, a negative electrode active material layer, a negative electrode current collector that collects current from the negative electrode active material layer, and a solid electrolyte layer disposed between the positive electrode active material layer and the negative electrode active material layer.
2. 2. The all-solid-state lithium ion battery according to claim 1, wherein the low melting point positive electrode current collector has a coating layer containing a carbon material on a surface on the positive electrode active material layer side.
3. The all-solid-state lithium ion battery according to claim 2 , wherein the coating layer contains an inorganic filler.
4. The all-solid-state lithium ion battery has a unit cell, The unit cell comprises: A negative electrode current collector; a first structure disposed on one surface of the negative electrode current collector; a second structure disposed on the other surface of the negative electrode current collector; having the first structure includes, in order from the negative electrode current collector side along a thickness direction, a first negative electrode active material layer, a first solid electrolyte layer, a first positive electrode active material layer, and a first positive electrode current collector, the second structure includes, in order from the negative electrode current collector side along a thickness direction, a second negative electrode active material layer, a second solid electrolyte layer, a second positive electrode active material layer, and a second positive electrode current collector, 4. The all-solid-state lithium ion battery according to claim 1, wherein at least one of the first positive electrode current collector and the second positive electrode current collector is the low melting positive electrode current collector.
5. The all-solid-state lithium ion battery has a plurality of unit cells, The plurality of unit cells are stacked in a thickness direction, 5. The all-solid-state lithium ion battery according to claim 1, wherein, in the plurality of stacked unit cells, when a positive electrode current collector located on the outermost side is an outermost positive electrode current collector, only the outermost positive electrode current collector is the low melting positive electrode current collector.
Citation Information
Patent Citations
All solid lithium secondary battery and method of manufacturing the same
JP2009164059A
Electrode for all-solid lithium battery, all-solid lithium battery and apparatus
JP2009289534A
Electrode for all-solid-state battery and all-solid-state battery
JP2014170655A
Fluoride ion battery
JP2018073753A
Electrode current collector and all solid state battery
JP2018200784A